Knowledge, attitudes, and practices of people living in artisanal mining areas on water pollution in Siguiri, Guinea, 2023 - Toure, Aly Badara; Diallo, Mariama Sadjo; Sidibe, Sidikiba; Bangoura, Salifou Talassone; Grovogui, Fassou Mathias; Diaby, Maladho; Bangoura, Mohamed Aly; Youla, Yamoussa; Kourouma, Mory; Delamou, Alexandre (Frontiers in Public Health, 2025)
IntroductionWater pollution is a major public health issue, especially in mining areas where artisanal mining activities are prevalent. The objective of this study was to analyze the knowledge, attitudes, and practices (KAP) of the population regarding water pollution in the mining areas of Siguiri, Guinea.MethodsA cross-sectional study was conducted from May 15 to June 15, 2023, on the population of Doko, Siguiri. Data were collected using a structured questionnaire that assessed knowledge, attitudes, and practices related to water pollution in artisanal mining areas. Logistic regression was used to analyze factors associated with KAP.ResultsThe survey included 501 respondents. Good knowledge of water pollution was observed in 53% of respondents, while 52% exhibited a positive attitude towards water pollution in artisanal mining area. Good practices were reported by 81% of respondents. The multivariate analysis showed that being educated (ORa: 2.13; 95% CI: 1.39; 3.29) and being a foreigner (ORa: 1.88; 95% CI: 1.04; 3.51) significantly associated with positive attitudes towards water pollution in artisanal mining area. Indeed, being single (aOR: 1.84; 95% CI: 1.10; 3.14), having good knowledge of water pollution (aOR: 2.51; 95% CI: 1.47; 4.36) and lack of lifestyle (tobacco and alcohol) (aOR: 2.51; 95% CI: 1.02; 5.97) were significantly associated with good practices.ConclusionThis study revealed moderate knowledge, positive attitudes and adequate practices regarding water pollution in Siguiri’s artisanal mining areas. However, significant gaps remain, including a lack of awareness of the risks associated with prolonged exposure to heavy metals. She advocates an integrated approach combining education, awareness-raising and technical support, accompanied by concrete solutions such as water treatment and the strengthening of community initiatives, in order to convert this knowledge into sustainable behavior.